Práticas do WhatsApp no Bom Dia Paraíba: novas rotinas produtivas no telejornalismo - Onofre, Raíssa Lima (2016)
The present study aimed at understanding how the journalistic practices are being rearranged in view of the use of the technological device Whatsapp in the productive routines of Bom Dia Paraíba, the news produced by TV Cabo Branco, affiliated to Rede Globo. It is assumed that journalists must be aware of the changes in communication brought by the media convergence, in a way that the newsrooms ought to be prepared to acquire the digital abilities demanded by the labour market. Based on these reflections, we sought to answer the question as follows: In what way the Whatsapp influences Bom Dia Paraíba productive routines? There was a contextualization on the topic followed by a more practical chapter based on a casestudy in which a researcher carried out a participant observation during a week in the News production. Therefore, we corroborated the theory Newsmaking, which states a social construction of reality. Authors such as Wolf (1994), Alsina (2009), Pena (2010), Paternostro (1999) and Jenkins (2013) were the main sources for this bibliographical and exploratory research. It was given focus on concepts about the articles production and media convergence, with emphasis on the relationship Whatsapp-telejournalism in the process of producing pieces of news for Bom Dia Paraíba. There have been identified along the field research five main influences on the use of Whatsapp in the TV news, listed as follows: 1. Whatsapp has contributed to speed up communication among the newsroom staff as it combines both personal and professional demands; 2. Expanded how the public and the TV news interact, bringing up a continual stream of access and interaction; 3. Depersonalized the flow of information to the extent that the Whatsapp is a “receptor” of informational contents which does not need a human to “receive” the contente through interaction; 4. Established anonymity to report in the journalistic routines through new ways to suggest agendas; 5. Increased the concern in verifying the information coming since the flow of information is uninterrupted. It is concluded that the app has positively changed the productivity within Bom Dia Paraíba, in spite of being a new tool and which has been reconfigured constantly.